The roles of ERIANIN in tumor and innate immunity and its’ perspectives in immunotherapy - Yang, Zhen; Liu, Ruxue; Qiu, Minghan; Mei, Hanwei; Hao, Jie; Song, Teng; Zhao, Ke; Zou, Dandan; Wang, Huaqing; Gao, Ming (Frontiers in Immunology, 2023)
Traditional Chinese medicine has been used in China for thousands of years. In 2022, the 14th Five-Year Plan for the Development of Traditional Chinese Medicine was released, aiming to enhance traditional Chinese medicine health services and improve policies and systems for high-quality traditional Chinese medicinal development by 2025. ERIANIN, the main component of the traditional Chinese medicine Dendrobium, plays an important role in anti-inflammatory, antiviral, antitumor, antiangiogenic, and other pharmacological effects. ERIANIN has broad-spectrum antitumor effects, and its tumor-suppressive effects have been confirmed in the study of various diseases, such as precancerous lesions of the stomach, gastric cancer, liver cancer, lung cancer, prostate cancer, bladder cancer, breast cancer, cervical cancer, osteosarcoma, colorectal cancer, leukaemia, nasopharyngeal cancer and melanoma through the multiple signaling pathways. Thus, the aim of this review was to systematically summarise the research on ERIANIN with the aim of serving as a reference for future research on this compound and briefly discuss some future perspectives development of ERIANIN in combined immunotherapy.